Nitrogenous compounds balance and microbial protein synthesis in steers supplemented with sunflower crushed in partial replacement of soybean meal - doi: 10.4025/actascianimsci.v35i3.18654 - Lima, Hellen Leles; Goes, Rafael Henrique de Tonissi e Buschinelli de; Oliveira, Euclides Reuter de; Gressler, Maria Gizelma de Menezes; Brabes, Kelly Cristina da Silva; Gabriel, Andrea Maria de Araújo (Acta Scientiarum. Animal Sciences, 2013)
Four steers in individual paddocks with Marandu grass (B. Brizantha) in 4x4 square design were used to evaluate sunflower crushed supplementation in pasture-grazing animals on nitrogen balance and microbial protein synthesis. Supplements at 6 g kg-1 body weight comprised corn, soybean meal, and mineral and soybean meal substituted at proportions 0, 20, 40 and 60%. Diet contained averages 6.79, 6.96, 7.10 and 6.87% nitrogen respectively for substitution levels 0, 20, 40 and 60%. The inclusion of sunflower crushed (SC) increased nitrogen intake and fecal excretion of nitrogen while providing a positive balance. Animals’ plasma urea concentration supplemented with SC was 28.13% lower than that of supplemented animals without SC. SC inclusion did not change allantoin concentration, purine derivatives, microbial nitrogen, crude microbial protein and microbial efficiency microbial, with mean rates totaling 150.98 mmol day-1; 158.06 mmol day-1, 112.35 g day-1, 702.18 g day-1; 146.41 crude protein (CP) microbial kg-1 of TDN. Partial replacement of soybean meal by sunflower crushed improves nitrogen balance without altering microbial protein synthesis and excretion of urea and creatinine